Oz the great and powerful - Weisz, Rachel, 1971-; Franco, James, 1978-; Williams, Michelle, 1980-; Kunis, Mila, 1983-; Braff, Zach, 1975-; Kapner, Mitchell; Lindsay-Abaire, David; Roth, Joe, 1948-; Raimi, Sam.; Curtis-Donen Productions; Walt Disney Pictures; Buena Vista Home Entertainment (Firm); et al. (Burbank, Calif. : Distributed by Buena Vista Home Entertainment, 2013)
Disney's fantastical adventure Oz The Great And Powerful, from the director of the Spider-Man trilogy, follows Oscar Diggs, a small-time circus magician with dubious ethics. When Diggs is hurled away to the vibrant Land of Oz, he thinks he's hit the jackpot--until he meets three witches who aren't convinced he's the great wizard everyone's expecting. Reluctantly drawn into epic problems facing Oz and its inhabitants, Oscar must find out who is good and who is evil before it's too late. Putting his magical arts to use through illusion, ingenuity--and even some wizardry --Oscar transforms himself into the great wizard and a better man as well.
Originally released as a motion picture in 2013.
Special features: bloopers; featurette "Walt Disney and the road to Oz", Walt's fascination with Oz.
Based on the works of L Frank Baum ; music by Danny Elfman ; film editor, Bob Murawski ; director of photography, Peter Deming.
Rachel Weisz, James Franco, Michelle Williams, Mila Kunis, Zach Braff.
MPAA rating: PG; for sequences of action and scary images, and brief mild language CHV rating: PG.
Blu-ray ; 1080p high definition ; Widescreen (beginning of features plays in 1.33:1) ; Surround sound.
Keywords: Wizard of Oz (Fictitious character) -- Drama; Oz (Imaginary place) -- Drama; Witches -- Drama; Action and adventure films; Fiction films; Feature films; Fantasy films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities